An investigation of earnings management and earnings manipulation in the UK - Marinakis, Pantelis (2011)
What causes managers to manipulate their financial statements? How best can shareholders or prospective investors, auditors, financial analysts and regulators detect earnings manipulations? Addressing these questions is of critical importance to the efficient functioning of capital markets. For an investor it can result to improved returns, for an auditor it can mean avoiding costly litigation, for an analyst it can mean avoiding a damaged reputation, and for a regulator it can lead to enhanced investor protection and fewer investment disasters. The objective of this thesis is two-fold. The first objective is to investigate the frequency and the magnitude of earnings management. Second, is to provide an analysis of the characteristics of companies discovered to manipulate earnings and the determinants of these manipulations.